Quality Control of Cement Bags Using Pareto Diagrams and Analytical Hierarchy Process (AHP) - marlina, winny alna (Jurnal Manajemen, 2023)
A cement company in Bengkulu which has been operating and producing premium quality cement since April 2015 is experiencing quality product issues, particularly regarding its cement bags. Raw material was the largest defect contributor, accounting for 65% of the total defective bags with the causing criteria were raw materials that did not meet specifications, no hole at the end of the valve, bags with poor adhesive strength, oversized bags, oversized pores of the bags, and the valve holes were too tight. Other defect contributor was related to machinery factor that contributed to 30% of the total defective bags with the causing criteria were conveyor belt sway, spout kick accuracy issue, poor guide plate accuracy, and loading machine with brake issues. Another defect contributor was related to human factor, that contributed to 5% of the total number of defects caused by human error such as lack of focus and fatigue. Pareto diagram was one of the seven tools in quality control. Pareto chart was a special type of bar chart where, each bar represented a different category or part of a problem. The sample used in this study was the number of defective cement bags (40 kg and 50 kg of cement bags) for the period of January-December 2019.